Discovery of the first Tn630 member and the closest homolog of IS630 from viruses - Yanping Hu; Guangyou Duan; Haohao Yan; Yutong Guo; Jia Chang; Mingbing Zhou; Shuangyong Yan; Wenjing Li; Cihan Ruan; Shan Gao (Scientific Reports)
Abstract IS630/Tc1/mariner (ITm) represents the most widely distributed superfamily of DNA transposons in nature. Currently, bioinformatics research on ITm members primarily involves collecting data of existing and emerging members and organizing them into new groups or families. In the present study, our survey revealed that Tc1 and IS630 members have a broad host range, spanning across all six biological kingdoms (bacteria, fungi, plantae, animalia, archaea and protista) and viruses. The primary discoveries include the first Tn630 member—Tn630-NC1 and the closest homolog of IS630 from viruses—Tc1-C#1. By incorporating our discoveries into existing knowledge, we proposed a model to elucidate the formation of composite transposons. Organization of Tc1 and IS630 members into groups across biological kingdoms facilitates data collection for future research, particularly on their horizontal transfer between different kingdoms. The formation of composite transposons may result from asymmetric of terminal inverted repeats. IS630 should be merged with Tc1 into a single family IS630/Tc1. Furthermore, IS630 and its homologs constitute a valuable resource for studying horizontal gene transfer between gut bacteria and phages, opening up new avenues for research in this field.